2013
DOI: 10.1088/0256-307x/30/3/036201
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Micro-Scale Plastic Deformation Feature on a Bulk Metallic Glass Surface under Laser Shock Peening

Abstract: Laser shocking peening is a widely applied surface treatment technique that can effectively improve the fatigue properties of metal parts. We observe many micro-scale arc plastic steps on the surface of Zr47.9Ti0.3Ni3.1Cu39.3Al9.4 metallic glass subjected to the ultra-high pressure and strain rate induced by laser shock peening. The scanning electronic microscopy and atomic force microscopy show that the arc plastic step (APS) has an arc boundary, 50-300 nm step height, 5-50 m radius and no preferable directio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…These features are consistent with our previous results for the sample alloy with 5 mm thickness. 11 The morphology of the deformed region for the thin sample after peening is shown in Fig. 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These features are consistent with our previous results for the sample alloy with 5 mm thickness. 11 The morphology of the deformed region for the thin sample after peening is shown in Fig. 2.…”
Section: Resultsmentioning
confidence: 99%
“…With a coupling pressure analytical method, the pressure transmitted to the BMG through shock wave was estimated to have a peak value about 8?2 GPa and full width at half maximum about 35 ns. 11,12 Moreover, the time (t), when the elastic precursor wave reaches the free back end of the sample, is calculated by t~h c~h…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into account the laser-MG interaction, the explanation based on the re-activation of pre-existing shear bands inside the sample could also be adopted to rationalize the observed behavior of the laser-irradiated surface. Previous studies [20,37,38] reported that after laser shock peening of a MG coated by aluminum foil as absorption layer and immersed in water to limit the plasma expansion, large amounts of shear bands appeared on the MG surface. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Wei et al performed LSP on Zr-based BMG, finding that numerous arc shearing steps with height of 50-300 nm formed on the treated surface. 11,12 The distribution of the residual stress characterized by Finite element analysis (FEA) revealed that the LSP could obviously improve the plasticity of BMGs. 13 Based on the results mentioned above, it is expected that the LSP could induce an extremely deep deformation region within BMGs, thus LSP could not only improved the plasticity of BMGs obviously, but also give the chance to investigate the structure evolution in the deformation region.…”
Section: Introductionmentioning
confidence: 99%